The Assistance In Developing Teaching Material For Sciences Teachers In Solok Selatan District Through Concept Review Based On Local Wisdom - Hufri Hufri (Fakultas MIPA Universitas Negeri Padang, 2020)
Solok Selatan district is located at an altitude of 350-430 meters above sea level. The landscape varies between lowlands, hills and highlands which are a series of Bukit Barisan mountains. Solok Selatan district is faced with complex environmental problems. The practice of illegal logging in forest areas and illegal gold mining along the Batang Hari and Batang Sangir streams on a large scale, so that the district of Solok Selatan is often hit by natural disasters. In addition this also caused damage to infrastructure and fatalities. This event was triggered by the low awareness and level of education of the community about the importance of environmental preservation. This is also shown from the level of Human Development Index (HDI) of Solok Selatan regency for 2017 which is 67.81 lower than the Province of West Sumatera which is 71.24. It can also be seen from the results of the 2016 National Examination ranking which is ranked 16th, with an average value of 49.18. The objectives of this activity and the targets set are to assist teachers in developing teaching materials through the concept review based on local wisdom. The method used consists of the observation phase, the orientation and discussion phase, the preparation phase for implementation, the implementation phase, the monitoring and evaluation stage as well as the data analysis and report stage. The instrument used was a science concept study test based on local wisdom and a questionnaire for the implementation of activities. The instrument used was a test on the concept review and local wisdom and the questionnaires for the implementation activities. The results of data analysis of the pretest and posttest, showed the average pretest score was 55.14, and the average posttest score was 67.18. From the paired t test, the significance result was 0.023 <0.05. So it can be concluded that the assistance activities in developing teaching material for sciences teachers have been able to improve the competence of science teachers in Junior High School in Solok Selatan district.